Physical and chemical effects of quartet structure (bamboo/zinc borate/shellac/surfactant) on organic coatings - Acarali, Nil; Demir, Sibel (ELSEVIER, 2021)
Bamboo was used owing to its properties as environmentally friendly and lightweight material. The purpose of this study was to increase hydrophobicity, flammability, gloss etc. by using additives (bamboo, shellac, zinc borate and surfactant) with different amounts (0-6%, w/w). Taguchi method was applied to reduce in the number of experiments by carrying out 16 experiments. As a result of the optimization studies, it was seen that the hydrophobicity of the water-based acrylic organic coating has increased from 39.52 degrees (reference coating) up to 104.32 degrees (optimum coating, Exp. No:15, Levels: 4-3-2-4). Shellac increased its homogenization and coating properties with its gloss property. In addition, zinc borate was preferred to increase its properties of flame retardancy, antimicrobial and nonwettable. Surfactant based methacrylate was used for dispersion of coatings. Thermogravimetric Analysis-Differential Thermal Analysis (TG-DTA), Scanning Electron Microscope (SEM), Contact Angle Measurement and physical test (adhesion, gloss, aging) results showed that the additives enhanced the thermal, morphological and physical properties of coatings and it could be evaluated in different areas of the construction industry.
Keywords: Bamboo; Shellac; Surfactant; Coating; Taguchi; PAINT; WATER; ADHESION; Chemistry